IMPROVING THE STUDENT’S READING SKIILL THROUGH SHORT STORY AT GRACE ENGLISH COURSE SIDAMANIK - DAME SETIA LAMTIUR PURBA; EVI ULI NATALIA SIDAURUK; REINA ADELINA SIPAHUTAR (CV KULTURA DIGITAL MEDIA, 2022)
Reading is the first way to know information, that’s why the success in learning a language at first can be seen from the ability of the learner’s to read the information from the book that they have read. However this is very hard for the beginner to read the foreigner language, especially English. There are a lot of reasons why they are very difficult in reading , such as lack of knowing difficult words to read, Lack of vocabulary to express their idea, Lack of chance to read and lack of interesting teaching method that can motivate them to read. This Research Proposal focuses on Improving Students’ reading Skill through Short Story at Grace English Course Sidamanik . The problem statement of this seminar : Is the short story effective in Improving Students’ reading skill at Grace English Sidamanik ? The goal of this research proposal is : to find out the effectiveness of short story in improving speaking skill at Grace English Course 1 Sidamanik. The population of this research is the students at Special Conversation Class (SPC) . The sample was taken by purposive sampling. The number of sample is 20 students. This research used pre-experimental method with pretest and posttest design. The pre-test given to know basic ability of the students reading skill and the post-test given to know the students’ improvement in reading skill after treatment. The result of this research shows that there is a significant improvement on students’ reading skill through short story at Grace English Course Sidamanik.